Pengamalan nilai-nilai Pancasila sebagai landasan etis dalam kebijakan perlindungan perempuan dari kekerasan seksual - Brahmandika, Leonard (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2024)
Pancasila is the ideology of the Indonesian nation, interpreted as an ethical system that contains moral values ​​that are the basis for creating social justice, harmony, and family. Lack of understanding and practice of Pancasila values ​​causes sexual violence. The purpose of this study is to examine in more depth how the practice of Pancasila values ​​as an ethical basis in policies to protect women from sexual violence. This study uses a descriptive method with data collection techniques through literature studies. The results of the study indicate that the practice of Pancasila values ​​is an effort to prevent acts of sexual violence. Pancasila values ​​contain awareness of moral attitudes and human behavior based on conscience and norms in society. Pancasila values ​​are used as a basis for making policies to protect women by paying attention to their rights as citizens. Cooperation between educational institutions, society and government in instilling Pancasila values ​​in society is very important. The aim is to provide an understanding to the public that it is important to practice Pancasila values ​​in life so that it can prevent acts of sexual violence.